ANALISIS KEBIJAKAN PENGEMBANGAN INDUSTRI KECIL KERAJINAN TOPENG KAYU DI KABUPATEN GUNUNGKIDUL - Mulyono, Heru (Jurnal Sains dan Teknologi Indonesia, 2007)
Medium and small industry sector has an important role, not only as a job provider for the number of job seekers that increases from year to year, but also for production and distribution of goods and services or society. The expectationtowards the contribution of this sector in creating employment, generating regional income and national income from foreign exchange has been increasing especially because of the industry's capacity to compete in the global market due to its use of local content in production. In the Gunung Kidul District there are some various products that have potential and prospect to be developed. Some of them even has penetrated the export market. The Agency of District Development Planning of Gunung Kidul District has identified and analyzed some products and has therefore determined 5 (five) products that have potential to become the region's competitiveproducts. These are (based on rank) : 1. Wood Mask Handicraft, 2. Bamboo Handicraft, 3. Stone Handicraft, 4. Dried Cassava (Gaplek), 5. Cattle. In this article, the writer provides suggestions to the Gunung Kidul District Government for theirpolicy making for the development of wood mask handicraft small industry.